An Econometric Validation of Malthusian Theory: Evidence in Nigeria - Musa Abdullahi Sakanko; Joseph David (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Rising population is an asset, provided, the skills of the workforce are used to the maximum extent. If not appropriately channelized, it can be a liability for a nation. A skilled and hardworking population can emerge as a foundation for a country’s development. This study examines the validity of Malthusian Theory in Nigeria using time series data from 1960 to 2016, employs the ARDL bound test techniques. The result shows that in the long-run, population growth and food production move proportionately, while population growth poses a depleting effect on food production in the short-run, thus validating the incidence of Malthusian impact in Nigerian economy in the short-run. The researcher recommended the government should strategize plans, which will further intensify family planning and birth control measure, compulsory western education and revitalization of the agricultural sector.DOI: 10.150408/sjie.v7i1.6461